2017
DOI: 10.1111/tri.13042
|View full text |Cite
|
Sign up to set email alerts
|

The time dependency of renal allograft histology

Abstract: Much of the complexity of the histological appearance of kidney transplant biopsies depends on the time at which the biopsies are obtained. It is well established that many elementary histological lesions and diagnoses have a time-dependent occurrence. While some "active" inflammatory lesions are noted primarily early after transplantation, other lesions are "chronic" and accumulate over time post-transplant, sometimes closely related to the prior active inflammatory lesions. With time after transplantation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
3
10
0
Order By: Relevance
“…It is well described that ABMR due to DSA is a waxing and waning process, which ultimately culminates in irreversible chronic lesions and graft failure. 18 Our multivariate models showed that the presence of HLA-DSA is more important for predicting outcome than reaching ABMR h , which corresponds to previous studies that showed an independent association of HLA-DSA and ABMR h with outcome. [19][20][21] This is not the case for HLA-DSA-negative patients with ABMR h , where our study suggests that this histology, in the absence of HLA-DSA, is often a transient phenomenon, without an increased risk of graft functional decline or graft failure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is well described that ABMR due to DSA is a waxing and waning process, which ultimately culminates in irreversible chronic lesions and graft failure. 18 Our multivariate models showed that the presence of HLA-DSA is more important for predicting outcome than reaching ABMR h , which corresponds to previous studies that showed an independent association of HLA-DSA and ABMR h with outcome. [19][20][21] This is not the case for HLA-DSA-negative patients with ABMR h , where our study suggests that this histology, in the absence of HLA-DSA, is often a transient phenomenon, without an increased risk of graft functional decline or graft failure.…”
Section: Discussionsupporting
confidence: 89%
“…18 Our multivariate models showed that the presence of HLA-DSA is more important for predicting outcome than reaching ABMR h , which corresponds to previous studies that showed an independent association of HLA-DSA and ABMR h with outcome. These patients had significantly fewer subsequent biopsies with ABMR h than HLA-DSA-positive patients, and less development of chronicity.…”
Section: Ta B L E 4 (Continued)supporting
confidence: 89%
“…To move in this direction, several key knowledge gaps need to be addressed. First a clear understanding of the natural histologic progression of ABMR in the setting of preformed and de novo DSA is critically needed to identify histologic, serologic, molecular, and/or clinical factors associated with inferior graft survival 12 . This will require a multicenter effort and close examination of both serial surveillance biopsies and clinically indicated biopsies in well-characterized patient cohorts who did and did not receive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the time post-transplantation and rejection activity, this condition can be classified as either acute/active or chronic. However, acute and chronic changes can exist within the same biopsy [19]. Importantly, although acute and chronic are clinical terms suggesting the time of onset of a disease, here, this classification reflects activity or inactivity, rather than time of biopsy.…”
Section: Pathology Of Renal Allograft Rejectionmentioning
confidence: 99%